Novel Composite Foam Concept for Head Protection in Oblique Impacts1 . Issue 10 (19th May 2017) - Mosleh, Yasmine; Vander Sloten, Jos; Depreitere, Bart; Ivens, Jan
Abstract : Rotational acceleration experienced by the head during oblique impacts is known to cause traumatic brain injuries. It is hypothesized that shear properties of a foam layer, used for head protection (e.g., protective helmet liners, headliners in cars) can be related to the extent of rotational acceleration transmitted to the head. Furthermore, it is hypothesized that by introducing anisotropy in a foam layer, rotational acceleration can be mitigated. In this study, an anisotropic composite foam concept is proposed to mitigate head rotational acceleration, hence reducing the risk of traumatic brain injuries. The composite foam concept introduces anisotropy in a foam at the "macro level", combining different densities of foam in layered and quasi‐fiber/matrix configurations. The performance of expanded polystyrene (EPS) composite foams in quasi‐static compression and combined shear‐compression loading and also linear and oblique impact experiments, has been compared with the performance of single layer EPS foam of similar thickness and density. The results of oblique head impact have been analyzed by global head injury criteria such as HIC, HICrot, and HIP. The composite foam concept demonstrates a great potential to be utilized in applications such as protective helmets due to the significant mitigation of brain injury risk. Abstract : In this study, an anisotropic composite foam concept is proposed to mitigate head rotational acceleration, hence reducing the risk of traumatic brain injuries in oblique impacts. The composite foam concept introduces anisotropy in a foam at the "macro level, " combining different densities of foam in layered and quasi‐fiber/matrix configurations. This concept can be used, for example, for helmets with complex shapes.